Nursing home director of nursing leadership style and director of nursing-sensitive survey deficiencies. Issue 3 (July 2016) - McKinney, Selina H.; Corazzini, Kirsten; Anderson, Ruth A.; Sloane, Richard; Castle, Nicholas G.
Abstract : Background: Nursing homes are becoming increasingly complex clinical environments because of rising resident acuity and expansion of postacute services within a context of historically poor quality performance. Discrete quality markers have been linked to director of nursing (DON) leadership behaviors. However, the impact of DON leadership across all measured areas of DON jurisdiction has not been tested using comprehensive domains of quality deficiencies. Purpose: The aim of this study was to examine the effects of DON leadership style including behaviors that facilitate the exchange of information between diverse people on care quality domains through the lens of complexity science. Methodology: Three thousand six hundred nine DONs completed leadership and intent-to-quit surveys. Quality markers that were deemed DON sensitive included all facility survey deficiencies in the domains of resident behaviors/facility practices, quality of life, nursing services, and quality of care. Logistic regression procedures estimated associations between variables. Findings: The odds of deficiencies for all DON sensitive survey domains were lower in facilities where DONs practiced complexity leadership including more staff input and shared decisional authority. DON quit intentions were aligned with higher odds of facility deficiencies across all domains. Practice Implications: Results supported the hypotheses that DONs using complexity leadership approaches by interacting more freely with staff, discussing resident issues, and sharing decision making produced better care outcomes from every DON sensitive metric assessed by Centers for Medicare and Medicaid Services. The mechanism linking poor quality with high DON quit intentions is an area for future research. Encouraging DON use of complexity leadership approaches has the potential to improve a broad swath of quality outcomes.